Religious non-governmental organizations and philanthropy in Indonesia - Alawiyah, Tuti (Indonesian Journal of Islam and Muslim Societies, 2013)
Religious non-governmental organizations (RNGOs) and philanthropic activitiesin Indonesia have a long history. They existed prior to the creation of the nationstate. Social, political and economic changes in this country have influenced thedevelopment of non-profit organizations for more than sixty years after the Inde-pendence of the Republic Indonesia in 1945. Modernization and developmentprojects during the President Suharto era influenced the development of Non-governmental organizations (NGOs). In more recent years, RNGOs have largelydeveloped as a response to the socio-economic crisis after the downfall of Presi-dent Suharto regime. Discovering the dynamics of RNGOs in a broader context ofnon-profit organizations in Indonesia provides insights into the strengths andweaknesses of philanthropic activism in recent years. An historical overview ofnon-profit organizations, legal structures, functions, and financial resources areamong the themes that are described in this paper.Organisasi Agama Non Pemerintah (RNGOs) dan kegiatan filantropi di Indonesiamemiliki sejarah yang panjang. Mereka ada sebelum penciptaan negara bangsa.Perubahan  sosial,  politik  dan  ekonomi  di  negara  ini  telah  memengaruhiperkembangan organisasi nirlaba selama lebih dari enam puluh tahun setelah Kemerdekaan Republik Indonesia pada tahun 1945. Modernisasi dan pembangunanproyek-proyek  selama  era  Presiden  Soeharto  memengaruhi  perkembanganorganisasi non-pemerintah (LSM). Dalam tahun-tahun terakhir, RNGOs sebagianbesar telah dikembangkan sebagai tanggapan terhadap krisis sosial-ekonomisetelah jatuhnya rezim Presiden Soeharto. Menemukan dinamika RNGOs dalamkonteks yang lebih luas dari organisasi nirlaba di Indonesia memberikan wawasanke dalam kekuatan dan kelemahan dari aktivisme filantropi dalam beberapa tahunterakhir. Sebuah gambaran sejarah organisasi non-profit, struktur hukum, fungsi,dan  sumber  daya  keuangan  adalah  salah  satu  tema  yang  dijelaskan  dalammakalah ini